Longer‐term effects of supervised physical activity on obstructive sleep apnea and subsequent health consequences. (2nd May 2021) - Berger, Mathieu; Barthélémy, Jean‐Claude; Garet, Martin; Raffin, Jérémy; Labeix, Pierre; Roche, Frédéric; Hupin, David
Abstract : Although recent trials have shown promising benefits of exercise on obstructive sleep apnea (OSA) severity, the long‐term effect of these interventions remains unknown. The aim of this study was to assess the effect of a 9‐month community physical activity program on OSA severity one year later in free‐living conditions. OSA patients, previously included in a 9‐month randomized controlled trial (EXESAS study) evaluating the effects of supervised community physical activity on OSA severity, were invited to participate in an extra one‐year observational study. Twenty‐eight patients completed the study. Although OSA severity did not significantly worsen over the real‐life period (9 to 21 months of follow‐up), reductions in apnea‐hypopnea index (AHI) and oxygen desaturation index were no longer significant after 21 months of follow‐up compared to baseline (baseline AHI: 22.2 ± 6.3 /h; 9 months: 16.3 ± 6.4 /h; 21 months: 18.7 ± 8.9 /h). Benefits observed at 9 months on daytime sleepiness and mental health were preserved at 21 months, whereas cardiorespiratory fitness slightly decreased. Per‐protocol analysis revealed that patients who stopped exercise at 9 months had worsened OSA severity compared to those who continued exercise during the real‐life period (AHI: +9.0 ± 8.8 vs. −1.3 ± 5.3 /h; p < .01). In conclusion, our study suggested that improvements in OSA severity remain transient and is dependent on long‐term adherence to regular physical activity practice.